2010
DOI: 10.1177/0333102409351797
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological-based childhood headache natural history study: After an interval of six years

Abstract: Headache is a common problem among adolescents, and variations can be observed in headache types and characteristics. The present study aimed to reach 5562 Turkish children who were investigated six years previously in a school-based childhood headache project, and to evaluate their current headache status. Investigators interviewed the available students with structured questionnaires. New and old data were matched and analyzed. The present study included 1155 adolescents (mean age 15.2 +/- 1.1 years), with 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
41
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(55 citation statements)
references
References 49 publications
10
41
0
4
Order By: Relevance
“…High persistence rates have also been reported in follow-up studies for longer periods (5–10 years) in which half to most (47–83.5%) of the school children still had headaches in adolescence [29, 30], whereas about one-quarter of young adults still reported headaches in longer follow-up evaluations (13–15 years) [31, 32]. To date, the longest follow-up studies of school-aged children were performed by Bille, who examined the course of pronounced migraine over 30–40-year intervals when about 50% of the participants were about 50 years of age and still experienced migraines [28].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…High persistence rates have also been reported in follow-up studies for longer periods (5–10 years) in which half to most (47–83.5%) of the school children still had headaches in adolescence [29, 30], whereas about one-quarter of young adults still reported headaches in longer follow-up evaluations (13–15 years) [31, 32]. To date, the longest follow-up studies of school-aged children were performed by Bille, who examined the course of pronounced migraine over 30–40-year intervals when about 50% of the participants were about 50 years of age and still experienced migraines [28].…”
Section: Discussionmentioning
confidence: 99%
“…In a reassessment of school children with no headache at baseline, Özge and colleagues [29] reported that three-quarters had developed some form of headache disorder at the 6-year follow-up. In longer follow-up studies of 14 and 26 years, 25.1% [8] and 12.2% [29] of school children had developed unspecified headaches, respectively. In a 16-year follow-up of children in a headache-free control group, 11% had developed migraine [28].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Headache, a frequently occurring disorder in children and adolescents, is the third most common illness-related cause of absence from school, resulting in substantial impairment among pediatric patients [1-4]. The majority of headaches in children and adolescents are not associated with structural or organic disease [5-7].…”
Section: Introductionmentioning
confidence: 99%